Freestream velocity correction in narrow channel - Mohd Saiah, Helmey Ramdhaney; Mohd Rafie, Azmin Shakrine; Romli, Fairuz Izzuddin (Faculty of Mechanical Engineering, Universiti Teknologi MARA, 2018)
An experimental study was done on the effect of boundary layer development to freestream velocity in a narrow channel tunnel. Fundamental boundary layer theories were applied in quantifying and estimating the changes in the freestream velocity along the tunnel. It was found that the measured and the estimated freestream velocities were in good agreement. The increase in the freestream velocity was found due to the boundary layer blockage effect. The experimental results demonstrated that the corrected freestream velocity had negligible effect on the boundary layer analysis but it nevertheless proved to be a significant effect on correlating the flat plate heat transfer experiments.